INDICATORS OF REPAIR TECHNOLOGY OF PARTS OF THE GEAR PUMP OF THE NSH-K MODIFICATION OF THE TRACTOR HYDRAULIC SYSTEM - Melyantsov, Petro; Losikov, Olexander; Sidorenko, Viktor (SWorld-Ger Conference proceedings, 2025)
The paper considers the issues of determining the repair manufacturability indicators of gear pump parts, which affect the repairability coefficient of parts, the complexity of repair operations and the cost of repairing the hydraulic unit. The goal is ac